2016
DOI: 10.1002/etc.3672
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of oil and water accommodated fractions used to conduct aquatic toxicity testing in support of the Deepwater Horizon oil spill natural resource damage assessment

Abstract: The Deepwater Horizon blowout resulted in the release of millions of barrels of crude oil. As part of the Trustees' Natural Resource Damage Assessment, a testing program was implemented to evaluate the toxicity of Deepwater Horizon oil and oil/dispersant mixtures to aquatic organisms from the Gulf of Mexico. Because of the variety of exposures that likely occurred, the program included 4 Deepwater Horizon oils, which encompassed a range of weathering states, and 3 different oil-in-water mixing methods, for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 28 publications
4
70
0
Order By: Relevance
“…Thus, the different rates of decrease observed between oil types can likely be explained in part by the different proportions of droplet oil in the WAFs. In addition, the density of our oils increased with increased weathering . As shown by Stokes’ law, the density of the dispersed droplets, along with droplet size, plays an important role in how fast a droplet will rise out of the water column, with less dense droplet oil rising faster than more dense droplet oil.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the different rates of decrease observed between oil types can likely be explained in part by the different proportions of droplet oil in the WAFs. In addition, the density of our oils increased with increased weathering . As shown by Stokes’ law, the density of the dispersed droplets, along with droplet size, plays an important role in how fast a droplet will rise out of the water column, with less dense droplet oil rising faster than more dense droplet oil.…”
Section: Resultsmentioning
confidence: 99%
“…However, the bottom 2 panels of Figure demonstrate that as concentrations decrease past a point where the droplet phase starts to become depleted, there is a shift in the dissolved‐phase PAH composition to include higher proportions of the less soluble PAH analytes. Because the PAH compositions of unfiltered HEWAFs and CEWAFs are generally maintained across dilutions and the PAH composition of unfiltered samples resembles the PAH composition of the starting oil , we can expect that the dissolved‐phase PAH composition will start to resemble that of the starting oil (and the unfiltered PAH composition) at very low concentrations. We see evidence for this in the bottom 2 plots of Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Negri et al () reported increased sensitivity of coral larvae that were co‐exposed to UV radiation and crude oil. Studies following the Deepwater Horizon oil spill documented significantly increased toxicity to both pelagic and estuarine fish species after co‐exposure to crude oil and UV radiation (Alloy et al , ; Stieglitz et al ; Sweet et al ); however, the Australian North West Shelf crude oil has a different composition of PAHs than the oil collected following the Deepwater Horizon oil spill (Forth et al , ), and UV radiation in Western Australia is expected to be more intense than in the Gulf of Mexico. Therefore, the aim of the present study was to characterize the photo‐induced toxicity of the Australian North West Shelf oil to black bream embryos and yellowtail kingfish embryos using ambient sunlight during the peak of Australia's summer.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation and chemical composition of the DWH artificially weathered MC252 oil used in this study are described in Forth et al (2016). Weathering of the oil resulted in the loss of the volatile, lighter weight PAH's, including BTEX compounds.…”
Section: Kl Pritsos Et Al Ecotoxicology and Environmental Safety Xmentioning
confidence: 99%